The Influence of Appraised Value, Costs, and Services on Customer Decisions to Use Sharia Gold Pawn Financing Services (Case Study at Bank Syariah Indonesia KCP Medan Sukaramai) - Irgi Iqbal; Tri Inda Fadhila Rahma; Nusantri Yanti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research aims to determine whether the estimated value, costs, and services affect the decision of customers to use Islamic gold pawn financing services at Bank Syariah Indonesia KCP Medan Sukaramai. The research method used in this study is quantitative research. The results of this study indicate that the estimated value, costs, and services simultaneously have no effect on customer decisions. With a coefficient of determination of 0.117 or 11.7%. The results of partial testing of variable X1 show that the estimated value has no positive effect on the decision of Islamic gold pawn customers at BSI KCP Medan Sukaramai, variable X2 shows that costs have no positive effect on the decision of Islamic gold pawn customers at BSI KCP Medan Sukaramai, and variable X3 shows that service has no positive effect on the decision of Islamic gold pawn customers at BSI KCP Medan Sukaramai.